PENINGKATAN PELAKSANAAN KESELAMATAN PASIEN PERIOPERATIF PERAWAT PELAKSANA MELALUI PENGENDALIAN KEPALA RUANGAN DI RS X - Aam Sumadi; Hanny Handiyani; Tuti Nuraini (Jurnal Afiat : Kesehatan dan Anak, 2019)
Introduction the risk of errors in the perioperative period is very large so that patient safety should be supported and the team is obligated to cooperate in raising awareness toward the occurrence of the incident or event that is not expected. Head nurse control function ensure appropriate planning objectives accomplished. The purpose aims to know the effectiveness of the control function of the head nurse toward the implementation of perioperative patient safety. This research method research design using preexperiment with pretest-posttest design without control. The sample size of 75 nurses that involved in perioperative nursing service. The results data analysis using paired t test represent the effectiveness of the control function of the head nurse with p value = 0.0001 (CI = 120.79 – 127.01) and the improve of implementation of perioperative patient safety by nurses. The conclusion post intervention that indicates positive correlation with p value = 0.0001 (CI = 141.59 – 147.15). Suggestions this research recommends there should be monitoring and evaluation of implementation of the control head room and a development model that is more complete control